2003
DOI: 10.1074/jbc.m207148200
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of the Progesterone Receptor and of the Steroid Receptor Coactivator SRC-1

Abstract: SUMO-1 (small ubiquitin-like modifier) conjugation regulates the subcellular localization, stability, and activity of a variety of proteins. We show here that SUMO-1 overexpression markedly enhances progesterone receptor (PR)-mediated gene transcription. PR undergoes a sumoylation at lysine 388 located in its N-terminal domain. However, sumoylation of the receptor is not responsible for enhanced transcription because substitution of its target lysine did not abolish the effect of SUMO-1 and even converted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
120
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 72 publications
7
120
0
Order By: Relevance
“…Consistent with this hypothesis, it was recently demonstrated that SUMO-1 overexpression markedly enhances progesterone receptor-mediated gene activation. However, despite the fact that the progesterone receptor was sumoylated, the sumoylation of the SRC-1 co-activator increased progesterone receptor-SRC-1 interaction and prolonged SRC-1 retention in the nucleus (39). Another attractive explanation comes from a recent study in which it was demonstrated that PIAS␥ interacts with histone deacetylase 1 and represses transforming growth factor-␤/ Smad-mediated transcription in an histone deacetylasedependent manner (40).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, it was recently demonstrated that SUMO-1 overexpression markedly enhances progesterone receptor-mediated gene activation. However, despite the fact that the progesterone receptor was sumoylated, the sumoylation of the SRC-1 co-activator increased progesterone receptor-SRC-1 interaction and prolonged SRC-1 retention in the nucleus (39). Another attractive explanation comes from a recent study in which it was demonstrated that PIAS␥ interacts with histone deacetylase 1 and represses transforming growth factor-␤/ Smad-mediated transcription in an histone deacetylasedependent manner (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also opposite examples of SUMO-modified proteins, which lead to transcriptional activation rather than repression. Transcriptional coactivators, such as SRC-1 and GRIP1, are shown to be modified by SUMO-1, thus resulting in enhanced transcriptional coactivator capacities (60,61). Therefore, sumoylation does not necessarily induce transcriptional repression depending on the substrates.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy, however, that in some contexts, the SUMO system has been shown to activate steroid receptors (Le Drean et al, 2002). This is most likely due to the modification of the nuclear receptor coactivators of the p160 family, such as Grip1/TIF2 and SRC-1 (Jimenez-Lara et al, 2002; Kotaja et al, 2002a;Chauchereau et al, 2003). Modification of these coactivators appears to facilitate interaction with the receptors and thereby enhances their transcriptional activity.…”
Section: Steroid Hormone Signallingmentioning
confidence: 99%